Designing a Service Provision Website Using the Design Thinking Method - Rasmila Rasmila; Dilla Nafasari (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2024)
Berkarya Abdi Sejahtera is a company that operates in the field of Outsourcing services such as Administration, Data Input, Operator, Warehouse, Labor, Security, Office Boy/Grill, Driver, Technician, Mechanic, and others. One way to increase company development is by using the website. Websites are increasing rapidly along with the number of websites that are used as a tool to promote companies to make them better known. Based on previous research conducted regarding Thrifdoor Business Website Design Using the Design Thinking Approach Method, it states that the creation process uses the Design Thinking method. The aim of this research is to create a website design by innovating using the Design Thinking method. and it is hoped that the design of this website will make it easier for companies to introduce their company. Observation is a process of observing and then recording systematically, logically, objectively and rationally regarding various phenomena in real situations, as well as artificial situations. The author collects and reviews data obtained by direct review and monitoring. Interviews are conducted to obtain data and information in the form of questions and answers from people who are directly involved with the system that is the object of research. Interviews will be conducted with members of PT Berkarya Abdi Sejahtera at the design stage. The 5 stages of design thinking: empathize, define, ideate, prototype, and test.